The wheel of time: The environmental dance of aged micro- and nanoplastics and their biological resonance - Hongjian Li; Lihua Bai; Sijia Liang; Xiru Chen; Xinyue Gu; Chao Wang; Cheng Gu (Eco-Environment & Health)
The aging of micro- and nanoplastics (MNPs) significantly affects their environmental behavior and ecological impacts in both aquatic and terrestrial ecosystems. This review explored the known effects of aging on MNPs and identified several key perspectives. Firstly, aging can alter the environmental fate and transport of MNPs due to changes in their surface properties. This alteration accelerates their accumulation in specific habitats like oceans and soils, resulting in increased bioaccumulation by organisms. In addition, aged MNPs interact differently with living organisms than their pristine counterparts by influencing the attachment of biofilms and other microorganisms in aquatic ecosystems. Moreover, the aging processes of MNPs exhibit adverse effects on aquatic and terrestrial organisms via increasing the bioavailability and potential toxicity of MNPs as degradation products are released. Last but not least, the biodegradation potential of MNPs can be altered by the aging process, thus affecting their degradation rates and pathways in the environment. However, there are still knowledge gaps regarding the natural aging behaviors of MNPs, such as the aging mechanisms of different types of plastic, the influence of environmental factors, the release of pollutants, and even the effects of aging on their transformation in different ecosystems. Therefore, a great contribution can be made to sustainable plastic use and environmental preservation by studying the natural aging of common MNPs and their subsequent biological effects.